Effect of Korean Medicine Treatment Focused on Acupotomy and Bee Venom Pharmacopuncture for Severe Lumbar Disc Herniation Requiring Surgery: Two Clinical Cases - Tae Rim Lee; Young Han Nam; Choong Hyun Han; Young Kyung Kim; Youn Young Choi; Jae Hui Kang; Hwa Yeon Ryu; Hyun Lee (Journal of Acupuncture Research)
This paper reports the treatment of two patients with severe lumbar herniated intervertebral disc (LHIVD) and lower limb weakness who required surgery. The patients underwent Korean medicine treatment, focusing on acupotomy and bee venom (BV) pharmacopuncture. Progress was assessed using the numerical rating scale (NRS), manual muscle test (MMT), and sensory examination of dermatomes. In Case 1, low back pain decreased from NRS 6 to 2, and lower limb pain from 6 to 1. The ankle MMT score returned to normal, and sensory scores improved in the L4 and L5 dermatomes. In Case 2, low back pain decreased from NRS 7 to 3, and lower limb pain from 7 to 2. The ankle MMT score normalized, and sensory scores improved across multiple dermatomes. This study is the first to report the efficacy of acupotomy and BV pharmacopuncture for severe LHIVD with muscle weakness, showing faster recovery compared to other approaches.